Формирование психологической готовности курсантов МЧС к профессиональной деятельности - Yakimenko Е. (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2012)
The aspects of readiness for professional activity, which is integrative in nature. Attention is paid to methods of psychological preparation for action in emergency situations, the specificity is determined by professional rescuers, firefighters. The features of the negative mental changes associated with the extreme conditions that influence the willingness to act in emergency situations. The results of diagnostic studies and comparative analysis of behavioral strategies in uncertain conditions of students of the 1st and 4th courses Command and Engineering Institute, Ministry of Emergency Situations of the Republic of Belarus with the assessment of prognostic features of decision-making and dynamic consistency with the current situation.